Corporate misuse of legal professional privilege: concealing and constituting crimes - Campbell, Liz (Evil corporations, 2025)
This chapter draws on two contemporary Australian case studies, of PricewaterhouseCoopers Australia and the Star Casino, to contend with the following questions: How is legal professional privilege (LPP) being used by corporates and regulators? Can this misuse conceal and/or constitute criminal behaviour? These two case studies exemplify how the misuse of privilege can stymie public enforcement actions. They highlight the central role of lawyers in this dynamic, and indicate how law reform is needed.